Determinação de impurezas elementares em suplementos alimentares por espectrometria de absorção atômica - Leal, Gabriela Camera (2018)
This work presents a study of the determination of arsenic, cadmium and lead in food supplements by atomic absorption spectrometry. Food supplements are obtained in synthetic form and derived from plants, and contamination of metals and metalloids may occur due to the industrial environment, soil geochemical characteristics, among other forms. The methods for the determination of Pb and Cd were developed in high resolution atomic absorption spectrometer with continuous source equipped with graphite furnace with direct sampling and the method for the determination of As was developed in atomic absorption spectrometer with generation of hydrides with decomposition of the samples by acid digestion. The concentration of lead, cadmium and arsenic were determined in 72 food supplements available in the Brazilian market. For the methods developed in HR-CS SS GFAAS the platforms were coated with Zr and the use of Pd(NO3)2 and Mg(NO3)2 with chemical modifiers presented better analytical performance. The performance parameters of the methods were in accordance with the standards of the American Pharmacopoeia for inorganic analysis in food supplements. The precision, expressed as relative standard deviation, was less than 5% for the HR-CS SS GFAAS methods and less than 6.1% for the HGAAS method, and the detection limits were 2.16 pg for Pb, 0.47 pg Cd and 0.37 μg/L As. The content of metals and metalloids in the samples ranged from 0.04 to 1.68 μg / g for Pb, 0.01 to 0.37 μg/g for Cd and As content varied from 0.02 to 0.73 μg/g. The American Famacopeia recommends limits of 10 μg / day Pb and 5 μg / day Cd. Four products had amounts of Pb above the allowed one and a sample had Cd above the acceptable amounts. Contamination of dietary supplements by these elements is of concern, even at low concentrations, since chronic exposure can cause serious deleterious health effects.